2020
DOI: 10.1111/cge.13725
|View full text |Cite
|
Sign up to set email alerts
|

Novel phenotype of syndromic premature ovarian insufficiency associated with TP63 molecular defect

Abstract: There is growing evidence that TP63 is associated with isolated as well as syndromic premature ovarian insufficiency (POI). We report two adolescent sisters diagnosed with undetectable ovaries, uterine hypoplasia, and mammary gland hypoplasia. A novel paternally inherited nonsense variant in TP63 [NM_003722.4 c.1927C > T,p. (Arg643*)] in exon 14 was identified by exome sequencing. One of the syndromes linked to TP63 is limb mammary syndrome (LMS), an autosomal dominant inherited disorder characterized by ectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Both the frameshift mutation p.Q568fs*3 and the nonsense mutation p.R594* fell within the SAM domain and truncated the TAp63α protein prior to the TID. Interestingly, these 2 mutations and 5 previously reported POI-related mutations were all heterozygous frameshift or nonsense mutations leading to the loss of all or part of the TID ( Figure 1A ) ( 26 29 ). In addition, the other 4 point mutations we identified (p.R643Q, p.L646P, p.R647C, and p.R655Q) were located in the conserved core sequence of the TID from R643 to R655 (RFTLRQTISFPPR), which is responsible for binding with the TAD ( Supplemental Figure 2 ) ( 16 ).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Both the frameshift mutation p.Q568fs*3 and the nonsense mutation p.R594* fell within the SAM domain and truncated the TAp63α protein prior to the TID. Interestingly, these 2 mutations and 5 previously reported POI-related mutations were all heterozygous frameshift or nonsense mutations leading to the loss of all or part of the TID ( Figure 1A ) ( 26 29 ). In addition, the other 4 point mutations we identified (p.R643Q, p.L646P, p.R647C, and p.R655Q) were located in the conserved core sequence of the TID from R643 to R655 (RFTLRQTISFPPR), which is responsible for binding with the TAD ( Supplemental Figure 2 ) ( 16 ).…”
Section: Resultsmentioning
confidence: 63%
“…In previous reports, heterozygous variants in the human TP63 gene were mostly shown to impair epidermal development and to cause multiple organ malformations, including 5 syndromic and 2 nonsyndromic disorders ( 25 ). Interestingly, a relationship has been identified between C-terminal variations of the TP63 gene and POI ( 26 29 ). The patients in these studies with TP63 mutations presented with syndromic or isolated POI, and these variants were frameshift or nonsense mutations leading to truncated C-termini, which might disrupt the autoinhibitory state of TAp63α and induce uncontrolled oocyte death ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…The sequencing was focused on 295 candidate genes selected from literature and our previous data. Through this approach, we could identify 9 already known variants ( 6 , 31 , 34 , 36 38 , 42 , 43 ) and 32 novel rare variants in genes already associated to POI etiology. Moreover, 34 novel rare variants have been found in additional genes participating in pathways important for ovarian physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one of the genetic interactors of armitage in Drosophila is the loki gene ( lok ) coding for the orthologue of the human CHEK2 , known to be an interactor of the previously identified TP63 array gene ( Bestetti et al , 2019 ) and found mutated in a new familial case of POI ( Mathorne et al , 2020 ). CHEK2 , defined as a guardian of female germline integrity ( Amelio et al , 2012 ; Xian and McKeon, 2018 ), is a multifunctional kinase involved in cell cycle checkpoint regulation, DNA repair and apoptosis ( Gebel et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%